HYBRID METHOD FOR INTEGRAL EVALUATION OF REGIONAL SYSTEMS EFFICIENCY (ON EXAMPLE OF THE SOUTHERN CITIES OF RUSSIA) - Selyutin В.В.; Zarutsky С.А.; Mesrobian К.Е. (Journal of Information Technologies in Education (ITE), 2012)
The paper proposes a hybrid technology for multidimensional ranking of complex socio-economic systems with many inputs and outputs. Two approaches are compared such as DEA model for objective separation of objects in efficient and inefficient and MCDM for subjective rankings. The combination of these two approaches enhances the quality of integral evaluation of complex systems. The case study of ranking of the cities of Southern Russia is presented.